Preparation and Adsorption Properties of a Biosorbent from Banana Peel for Use as Natural Vitamin Beads in Cosmetic Products - Dechprasitichok, Pornpassanan; Panichakul, Tasanee; Itsarasook, Khwunjit; Boonthoem, Napaporn; Sontag, Christoph; Luachan, Sanchai (Journal of Food Health and Bioenvironmental Science, 2023)
The purpose of this research was to produce natural vitamin beads using a biosorbent from banana peel as an alternative to plastic vitamin beads for use in cosmetic products. The new biosorbents could be prepared by an extraction process in combination with a hydrothermal technique and physical processing. The biosorbent material has high fiber content, up to 45.25% by weight, particle sizes in the range of 10-160 μm, with a specific surface area of 21.5 m2/g and a point of zero charge at pH 6.83. It has a high cellulose crystallinity index (Icr) equal to 59.2%. It could be manufactured with a yield of 8.85%. The study on the adsorption equilibrium of this biosorbent material showed that the Langmuir isotherm fits better for the adsorption process (R2 = 0.9912) than the Freundlich isotherm (R2= 0.9532) which presented a monolayer surface adsorption mechanism confirmed by XRD of vitamin C from released solution. The biosorbent from banana peel has an effective adsorption capacity for vitamin C (5% solution) of 545 mg/g and the release efficiency of vitamin C was 80% in water. In addition, an increase of adsorption capacity from 27 to 50 °C showed that the adsorption reaction between the biosorbent and vitamin C was endothermic. We have concluded that biosorbent from banana peel can be prepared by a hydrothermal method that is energy-efficient and environmentally friendly. This biosorbent material can be used as a natural alternative to polyethylene beads for vitamin C release in cosmetic products for antioxidant effect. The product from this research is a new category that combines natural materials with active ingredients to be used in cosmetic applications to ensure health safety and environmental protection.